A Systems Thinking Approach to Exploring the Influence of the Media on How Publics Engage With and Develop Dialogues Relating to Electric Vehicles - Esmene, Shukru; Taylor, Timothy J.; Leyshon, Michael (Frontiers in Communication, 2020)
Electric vehicles (EVs) are the most popular alternative to petrol and diesel vehicles and are becoming a central part of climate change mitigation strategies. This paper draws attention to how publics engage with communication strategies relating to EVs. By focusing on the interlinked relationships between an individual’s location, socio-demographic characteristics and their experiences with media sources, the paper demonstrates how EV-related knowledges are publicly engaged with and perceived by individuals. By using systems thinking as a critical analytical lens, we examine how these individuals use knowledges and/or refer to hegemonic framings of alternative technologies to discuss EVs. These constructs focus predominantly on consumerist framings of EVs and how they compare to petrol and diesel vehicles as a commodity. In this context, the paper provides an understanding of how to improve public engagement with EV-related communications by using a systems thinking approach. In doing so, the paper further offers a critical perspective on the relevance of EVs to publics beyond being a consumer product. These considerations can provide researchers with valuable insights into effective and more engaging communication strategies for particular contexts.